Future jobs in natural science and engineering: shortage or surplus? - Finn, Michael G.; Baker, Joe G. (Monthly Labor Review, 1993)
Studies conducted by the Oak Ridge Institute for Science and Education for the U.S. Department of Energy indicate that the projected average annual number of natural science and engineering degrees awarded between 1991 and 1997 will be approximately 20,000 fewer than needed to maintain the supply-demand balance of the 1984 to 1990 period. The market conditions experienced by natural science and engineering graduates in the late 1980s and early 1990s are likely to cause a decline in the number of young people who earn degrees in these fields. The projected decline in the number of these degrees awarded for the 1991-97 period is greater than the projected decline in the number of job openings in those fields. Nevertheless, if the study's projected supply and demand conditions materialize, a movement toward self-correction is likely, as upward pressure on salaries will eventually lead to higher degree awards rates in science and engineering.